Kelsen e l’omosessualità maschile - Gazzolo, Tommaso (Teoria e Critica della Regolazione Sociale / Theory and Criticism of Social Regulation, 2024)
The article is devoted to Kelsen’s interpretation of platonic eros. The analysis seeks to show how Kelsen’s confrontation with psychoanalysis is determined by his conception of homosexuality, inherited from the “style of reasoning” typical of late 19th-century psychiatry. The article seeks, finally, to show how, in Kelsen’s theory, the prohibition of homosexuality constitutes the material presupposition of any legal system.